Tissue iron quantification in chronic liver diseases using MRI shows a relationship between iron accumulation in liver, spleen, and bone marrow. Issue 2 (February 2018) - França, M.; Martí-Bonmatí, L.; Porto, G.; Silva, S.; Guimarães, S.; Alberich-Bayarri, Á.; Vizcaíno, J.R.; Pessegueiro Miranda, H.
Abstract : Aim: To investigate iron loading within the liver, pancreas, spleen, and bone marrow using magnetic resonance imaging (MRI) transverse relaxation rate (R2*), in patients with diffuse liver diseases; to evaluate the relationships between iron accumulation in these tissue compartments; and to assess the association between tissue iron overload and the pattern of hepatic cellular iron distribution (hepatocytes versus Kupffer cells). Material and methods: Fifty-six patients with diffuse liver diseases had MRI-derived R2* values, using a multi-echo chemical-shift encoded MRI sequence, of the liver, pancreas, spleen, and vertebral bone marrow. All patients had liver biopsy samples scored for hepatic iron grading (0–4) and iron cellular distribution (within hepatocytes only or within both hepatocytes and Kupffer cells). Results: Liver R2* increased with histological iron grade (RS =0.58, p <0.001) and correlated with spleen (RS =0.71, p <0.001) and bone marrow R2* (RS =0.66, p <0.001), but not with pancreatic R2* (RS =0.22, p =0.096). Splenic and bone marrow R2* values were also correlated (RS =0.72, p <0.001). Patients with iron inside Kupffer cells had the highest R2* in liver, spleen and bone marrow. Conclusions: Patients with chronic diffuse liver diseases have concomitant hepatic, splenic, and bone marrow iron loading. The highest hepatic iron scores and iron inside Kupffer cells were associated with the highest splenic and bone marrow deposits, suggesting systemic iron accumulation in the mononuclear phagocytic system. Highlights: Hepatic iron overload is common in chronic diffuse liver diseases. Liver iron overload occurs at both hepatocyte and mononuclear-phagocytic system. Hepatic, splenic and bone marrow R2* iron loading coexist in chronic liver diseases. Highest hepatic R2* values were found with highest splenic and bone marrow stores.